Successful Therapy for Myocarditis Concomitant With Complete Heart Block After Pembrolizumab Treatment for Head and Neck Squamous Cell Carcinoma: A Case Report With Literature Review - Su, Lina; Liu, Chuanfen; Wu, Wenjie; Cui, Yuxia; Wu, Manyan; Chen, Hong (Frontiers in Cardiovascular Medicine, 2022)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer therapy over the past decade. Despite their beneficial effects on treating numerous types of tumors, cardiotoxicity resulting from ICIs is a rare side effect but a concerning one due to its high mortality rate. We herein describe a case of an 80-year-old woman with recurrent head and neck squamous cell cancer (HNSCC), who presented with myocarditis complicated by complete atrioventricular block (CAVB) after second infusion of pembrolizumab. After quickly ruling out myocardial infarction and viral myocarditis, the strong relationship between the onset time and pembrolizumab therapy suggested that ICI-induced myocarditis was the most possible diagnosis. Though CAVB frequently presents with fulminant myocarditis in the setting of ICI-related cardiotoxicity, the patients kept a stable hemodynamic status and had normal myocardial function with just a slightly low global longitudinal strain (GLS) at -16.4%, which implied myocardial injury but was highly related to good prognosis based on the existing literature. Besides, elderly patients are vulnerable to adverse outcomes of steroid therapy, notably opportunistic infections. To balance beneficial effects and adverse effects of immune suppression, she accepted high-dose steroids without pulse methylprednisolone. Excitingly, she had a dramatic clinical and laboratory improvement, and heart block quickly returned to normal sinus rhythm. Another interesting finding was that the patient’s tumor remained stable during the half-year follow-up from the termination of immunotherapy. Besides, we here firstly review previously reported cases in terms of their clinical characteristics and prognosis of ICI-induced myocarditis with CAVB, in particular the reversibility of heart block. In conclusion, ICI-induced myocarditis can be life-threatening and it therefore warrants efforts to increase awareness, facilitate early detection, and initiate prompt intervention. Importantly, CAVB secondary to ICIs-induced myocarditis may not always present with fulminant myocarditis and more than 50% of these surviving patients might recover to normal sinus rhythm. For patients with ICI-induced myocarditis with contraindication for cardiac magnetic resonance (CMR), speckle-tracking echocardiography is a reliable and sensitive alternative to CMR for detecting myocardial injury, and GLS may be an important prognostic indicator.